Some well-known inequalities of Ostrowski like for Caputo derivatives - Yonghong Liu; Ghulam Farid; Jongsuk Ro; Mawahib Elamin; Sayed Abdel-Khalek (Applied Mathematics in Science and Engineering)
This paper aims to provide new versions of some known inequalities by applying Caputo fractional derivatives. Ostrowski, Hermite-Hadamard and Ostrowski-Grüss-type inequalities are given. Generalized conditions of existing inequalities are analysed to get new inequalities. Special cases are discussed to prove the general nature of former inequalities.